2015
DOI: 10.1161/hypertensionaha.115.05851
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between 24-Hour Salt Ingestion and Sodium Excretion in a Controlled Environment

Abstract: Accurately collected 24-hour urine collections are presumed to be valid for estimating salt intake in individuals. We performed two independent ultra-long-term salt balance studies lasting 105 (4 men) and 205 (6 men) days in 10 men simulating a flight to Mars. We controlled dietary intake of all constituents for months at salt intakes of 12, 9, and 6 grams per day and collected all urine. The subjects’ daily menus consisted of 27,279 individual servings, out of which 83.0% were completely consumed, 16.5% compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
156
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(162 citation statements)
references
References 31 publications
3
156
0
3
Order By: Relevance
“…A similarly interesting question is how sodium transport takes place between the subcutaneous stores and the lymphatic vessels. It is imaginable that this recruitment of salt from these stores is a regulated process (95). In that case, it may very well involve Na ϩ transporters that are similar to transporters in the kidney to facilitate movement of sodium from the intercellular space back into the lymphatic vessels.…”
Section: F966mentioning
confidence: 99%
“…A similarly interesting question is how sodium transport takes place between the subcutaneous stores and the lymphatic vessels. It is imaginable that this recruitment of salt from these stores is a regulated process (95). In that case, it may very well involve Na ϩ transporters that are similar to transporters in the kidney to facilitate movement of sodium from the intercellular space back into the lymphatic vessels.…”
Section: F966mentioning
confidence: 99%
“…We recently reported ultra-long-term balance studies in 10 healthy young men simulating a flight to Mars (11,12). We found that Na + was rhythmically stored and released with about-weekly (circaseptan) and circa-monthly (circalunar) periodicity.…”
Section: Introductionmentioning
confidence: 98%
“…Equally there is a significant body of evidence demonstrating that reducing salt consumption can be effective in lowering blood pressure, with projected large benefits for cardiovascular mortality and medical expenditure (3,4) . Collection of 24 h urine samples is the preferred method for determining population salt intake (5) although it does not capture the approximate 10 % of dietary salt lost through non-urinary routes (6) . In Australia, a number of small studies have measured salt consumption using 24 h urine samples but no nationally representative study has been conducted using this method (7)(8)(9)(10)(11)(12) .…”
mentioning
confidence: 99%